The comparison of contrast-enhanced ultrasound and gadoxetate disodium-enhanced MRI LI-RADS for nodules ≤2 cm in patients at high risk for HCC: a prospective study - Qin, Zhengyi; Zhou, Yan; Zhang, Xiang; Ding, Jianmin; Zhou, Hongyu; Wang, Yandong; Zhao, Lin; Chen, Chen; Jing, Xiang (Frontiers in Oncology, 2024)
Objectives: To investigate the consistency of LI-RADS of CEUS and EOB-MRI in the categorization of liver nodules ≤2cm in patients at high risk for HCC.Methods: Patients at high risk for HCC with nodules ≤2cm who underwent CEUS and EOB-MRI in our hospital were prospectively enrolled. The CEUS images and EOB-MRI imaging of each liver nodule were observed to evaluate interobserver consistency and category according to CEUS LI-RADS V2017 and CT/MRI LI-RADS V2017 criteria double blinded. Pathology and/or follow-up were used as reference standard.Results: 127 nodules in 119 patients met the inclusion criteria. The Inter-observer agreement was good on CEUS and EOB-MRI LI-RADS (Kappa = 0.76,0.76 P < 0.001).The inter-modality agreement was fair (Kappa=0.21, P < 0.001). There was no statistical difference of PPV and specificity between CEUS and EOB-MRI LR-5 for HCC, while the difference of AUC was statistically significant. We used a new criteria (CEUS LR-5 and EOB-MRI LR-4/5 or CEUS LR-4/5 and EOB-MRI LR-5) to diagnose HCC. The sensitivity, specificity and AUC of this criteria was 63.4%,95.6% and 0.80.Conclusions: CEUS and EOB-MRI showed fair inter-modality agreement in LI-RADS categorization of nodules≤2cm. The inter-observer agreement of CEUS and EOB-MRI LI-RADS were substantial. CEUS and EOB-MRI LR-5 have equally good positive predictive value and specificity for HCC≤2cm, and combining these two modalities may better diagnose HCC≤2cm.